Sensitivity of Pushover Curve to Material and Geometric Modelling—An Analytical Investigation. (June 2015) - Panandikar (Hede), Neena; Narayan, K.S. Babu
Abstract: Nonlinear static analysis or pushover analysis developed over the last two decades and became the preferred procedure for design and seismic performance evaluation, as this procedure is relatively simple and considers post-elastic behaviour. It provides information on seismic demands imposed by the design ground motion on the structural system and its components. Generation of pushover curve from analysis for reinforced concrete structure involves tremendous amount of computational efforts as the input data for analysis itself is quite exhaustive. The analysis results are very sensitive to the techniques employed in geometric and material modelling. This paper envisages presenting the sensitivity of pushover analysis results to geometric and material modelling parameters by comparing the analysis results with that of experimental investigations. Attempt has been made to understand the sensitivity of parameters like variation in material properties, inaccuracies in placement of reinforcement, effect of confinement of concrete and modelling techniques for elements and plastic hinges. SAP-2000 has been utilised in the current investigation and results have been highlighted suggesting strategies to enhance pushover analysis capabilities.